Heart rate change as a predictor of treatment outcome for ring-coil accelerated low frequency repetitive transcranial magnetic stimulation in major depressive disorder: An exploratory study - Jack Z. Sheen; Jean-Philippe Miron; Helena Voetterl; Farrokh Mansouri; Ryan Zhou; Thomas Russell; Molly Hyde; Linsay Fox; Zafiris J. Daskalakis; John D. Griffiths; Daniel M. Blumberger; Jonathan Downar (Journal of Affective Disorders Reports, 2023)
Background and objective: High frequency (HF) left dorsolateral prefrontal cortex (L-DLPFC) rTMS has been reported to induce mild, transient bradycardia in patients with major depressive disorder (MDD), measured using electrocardiography (ECG). Low frequency (LF) rTMS has distinct advantages compared to HF rTMS and our previous investigation of a similar design suggested that heart rate (HR) may have biomarker potential for LF rTMS in MDD patients. Our previous study supported the utilization of HR biomarkers for LF-rTMS in MDD and thus this exploratory replication study aims to further investigate, in a different cohort and with a different coil, the effect of 1Hz right hemisphere (R)-DLPFC rTMS on the HR of MDD patients, as well as the potential of using HR as a simple, scalable biomarker to predict rTMS treatment response. Methods: 24 participants underwent 30 sessions of accelerated 1Hz R-DLPFC rTMS within 7 days after the baseline ECG session, followed by 20–25 once-a-day sessions 7 days after. The Beck Depression Inventory-II score was used as the primary outcome measure. Results: HR significantly decreased during the first 3 min of the rTMS period. Resting HR, HR during rTMS, and the degree of HR reduction were not significantly associated with treatment outcome. Conclusion: The results of the current study remain in concordance in trend with that of our previous study despite the use of a less accurate rTMS coil. Therefore, this study further supports the biomarker potential of HR for LF-rTMS in MDD patients.